Enhancing Awareness of Infection Prevention and Control among Healthcare Professionals: A Systematic Review - Meshari Hamed Fayez Altaweel; Ali Fahad Abdullah Al Munyif; Moneef Saleh Ali Almoneef; Ali Bin Awadh Bin Fadhil Alamri; Hamad Abdulhadi Saleh Almuneef; Abdulrahman Meshal Abdulrahman Almalawi; Hassan Mohammed Hassan Kamili (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: The effectiveness of infection prevention and control (IPC) measures is heavily reliant upon the knowledge and practices of healthcare personnel regarding these protocols. Following IPC measures is very important for protecting healthcare workers (HCWs), protecting patients, and providing safe services. Aim: This article aims to review literature addressing HCWs’ understanding of IPC protocols and identify factors that may influence compliance with IPC guidelines. Methods: An extensive list of electronic repositories (PubMed, Embase, WOS, Scopus) from 2009, to 2023. Results: HCWs demonstrate good, decent, and sometimes high levels of knowledge of IPC principles, including standard precautions, hand hygiene, and behaviors associated with urinary catheter use. However, significant knowledge deficiencies were found regarding HCWs’ knowledge of occupational vaccinations, infectious disease transmission, and the risk of needle stick and sharps injuries. The discussion examines the reasons responsible for the violation of IPC guidelines and recommends ways to improve compliance with such policies. Abstract: Adopting a comprehensive approach to change IPC intervention strategies is encouraged. The primary goal is to increase adherence to IPC guidelines among HCWs.